2011
DOI: 10.1002/tox.20720
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative and antigenotoxic effect of vitamin E against patulin cytotoxicity and genotoxicity in HepG2 cells

Abstract: Patulin (PAT) is a mycotoxin produced in fruits, mainly in apples, by certain species of Penicillium, Aspergillus, and Byssochlamys. It has been shown that PAT is cytotoxic, genotoxic, and mutagenic in different cell types. Several studies incriminate the oxidative stress as a mechanism of PAT-mediated toxicity. In this context, our aim was to investigate the protective role of Vitamin E (Vit E), an antioxidant agent, against PAT induced cytotoxicity and genotoxicity in cultured HepG2 cells. The obtained resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 66 publications
3
19
0
2
Order By: Relevance
“…Vitamin E is a group of fatsoluble compounds, including d-alpha-tocopherol, which has strong antioxidant activity [44]. Our result is consistent with previous studies that demonstrated the protective effects of vitamin E against the genotoxicity of several agents such as deltamethrin and patulin [45,46]. Thus, vitamin E has the potential to be used as a protective drug against the genotoxicity associated with mutagenic agents and diseases.…”
Section: Discussionsupporting
confidence: 92%
“…Vitamin E is a group of fatsoluble compounds, including d-alpha-tocopherol, which has strong antioxidant activity [44]. Our result is consistent with previous studies that demonstrated the protective effects of vitamin E against the genotoxicity of several agents such as deltamethrin and patulin [45,46]. Thus, vitamin E has the potential to be used as a protective drug against the genotoxicity associated with mutagenic agents and diseases.…”
Section: Discussionsupporting
confidence: 92%
“…There are a number of research studies examining the toxicity of PAT in mammalian cells. They demonstrated that PAT induces oxidative DNA damage, chromosome aberrations, and micronucleus formation [9][10][11][12][13]. Other investigators studied the in vivo administration of PAT and revealed that kidney, liver, intestinal tissue, and immune system as its target organs [14,15].…”
Section: Patulinmentioning
confidence: 99%
“…149,154 PAT'nin indüklediği oksidatif stresi ve kromozomal anormalliklerini azaltmaya yönelik son yıllarda yapılan çalışmalarda, antioksidan ve antigenotoksik maddelerin bu olumsuz etkileri düzel-tebildiği gösterilmiştir. [155][156][157] ALTERNARİA TOKSİNLERİ Alternaria toksinleri, Alternaria cinsi özellikle de Alternaria alternata tarafından üretilen sekonder metabolitlerdir. Bu mikotoksinler bitkilerde birikerek gıda üretim zinciri içerisinde yer almaktadır.…”
unclassified